Surgical Options for the Refractive Correction of Keratoconus: Myth or Reality - L. Fernández-Vega-Cueto; V. Romano; R. Zaldivar; C. H. Gordillo; F. Aiello; D. Madrid-Costa; J. F. Alfonso (Journal of Ophthalmology)
Keratoconus provides a decrease of quality of life to the patients who suffer from it. The treatment used as well as the method to correct the refractive error of these patients may influence on the impact of the disease on their quality of life. The purpose of this review is to describe the evidence about the conservative surgical treatment for keratoconus aiming to therapeutic and refractive effect. The visual rehabilitation for keratoconic corneas requires addressing three concerns: halting the ectatic process, improving corneal shape, and minimizing the residual refractive error. Cross-linking can halt the disease progression, intrastromal corneal ring segments can improve the corneal shape and hence the visual quality and reduce the refractive error, PRK can correct mild-moderate refractive error, and intraocular lenses can correct from low to high refractive error associated with keratoconus. Any of these surgical options can be performed alone or combined with the other techniques depending on what the case requires. Although it could be considered that the surgical option for the refracto-therapeutic treatment of the keratoconus is a reality, controlled, randomized studies with larger cohorts and longer follow-up periods are needed to determine which refractive procedure and/or sequence are most suitable for each case.